Criminology and criminal justice in post-devolution Wales - Jones, Robert (European journal of criminology, 2022)
This survey provides one of the first comprehensive reviews of Wales?s role in the England and Wales criminal justice system. The article explains that executive devolution has been responsible for a major transformation to Wales?s position within the England and Wales jurisdiction. Attention is given to the institutions responsible for criminal justice since devolution to Wales as well as an overview of some of the key trends and latest data, including recent research which shows that Wales, when disaggregated from England, has the highest rate of imprisonment in Western Europe. In light of the developments that have taken place over the past two decades, this survey asserts that Wales must now be taken seriously as a distinct and worthwhile unit of criminological analysis. It is argued that future research on Wales can help to develop a more constitutionally literate criminological debate across the UK as well as European regions affected by devolution.